Consumismo e sustentabilidade, um paradoxo para os profissionais de marketing - Braga, Afonso Carlos (2014)
The present dissertation addressed the sustainability challenges, under the planet environmental limitations point of view, to meet the corporations continuous profit and revenue growth objectives as well a potential paradox that some marketing executives have been facing, considering he/she is responsible to lead the communication initiative that many times encourages 'consumerism'. The idea was to understand if this topic is relevant to these professionals, hence their companies, and raise some hypotheses on how to approach this problem in order to provoke those companies to practice conscious marketing . Moving one step further, the type of organizational paradigm in which the executive s company acts influenced the way to approach this professional when conducting the personal interviews to collect data. Considering that, three organizational paradigms were considered: Funcionalism, Interpretativism and Radical Humanism. The cross analysis of existing marketing theories and how those professionals envisioned facing the challenges mentioned above revealed points and suggestions for future marketing strategiess